Psychometric properties of engagement in cultural-related diversity experiences among undergraduate students in Malaysian higher education institutions: a confirmatory factor analysis - Yunus, Norzita; Tamam, Ezhar; Bolong, Jusang; Adzharuddin, Nor Azura; Ibrahim, Faridah; Sayed Halem Shah, Dil Froz Jan (Elsevier, 2014)
The purpose of this study was to examine the psychometric properties of the items used to measure engagement in cultural-related experiences among local undergraduate students in Malaysian higher education institutions (HEIs). Engagement in cultural-related experiences has two forms: informal cross-national interaction (ICNI) and curricular/ co-curricular diversity (CD). In determining the internal consistency and construct validity of the items, the Cronbach's alpha reliability analysis, exploratory factor analysis and confirmatory factor analysis were applied. The Cronbach's alpha values for both ICNI and CD models were good. The values indicated very good construct reliability and adequate convergent validity. This study suggested that the ICNI 10-items model and CD 6-items model have a good fit and shown good psychometric values.